2019
DOI: 10.1016/j.psychres.2018.02.032
|View full text |Cite
|
Sign up to set email alerts
|

The intra-day dynamics of affect, self-esteem, tiredness, and suicidality in Major Depression

Abstract: Despite growing interest in the temporal dynamics of Major Depressive Disorder (MDD), we know little about the intra-day fluctuations of key symptom constructs. In a study of momentary experience, the Experience Sampling Method captured the within-day dynamics of negative affect, positive affect, self-esteem, passive suicidality, and tiredness across clinical MDD (N= 31) and healthy control groups (N= 33). Ten symptom measures were taken per day over 6 days (N= 2231 observations). Daily dynamics were modeled v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 66 publications
5
56
0
1
Order By: Relevance
“… 51 Similarly, daily suicide ideation predicted affective lability at baseline in individuals with BPD, 52 and associations between daily dissociations and suicide risks measured at baseline in adolescent girls with BPD. 53 Crowe, Daly 54 was one study that found people with MDD reported greater increases of daily affect and higher fluctuations in suicidality than people without MDD. Similarly, the study by Hallensleben, Glaesmer 55 found daily depressive symptoms, hopelessness, and perceived burdensomeness were significantly associated with passive and active suicidal ideation in people diagnosed with unipolar depression.…”
Section: Resultsmentioning
confidence: 99%
“… 51 Similarly, daily suicide ideation predicted affective lability at baseline in individuals with BPD, 52 and associations between daily dissociations and suicide risks measured at baseline in adolescent girls with BPD. 53 Crowe, Daly 54 was one study that found people with MDD reported greater increases of daily affect and higher fluctuations in suicidality than people without MDD. Similarly, the study by Hallensleben, Glaesmer 55 found daily depressive symptoms, hopelessness, and perceived burdensomeness were significantly associated with passive and active suicidal ideation in people diagnosed with unipolar depression.…”
Section: Resultsmentioning
confidence: 99%
“…The remainder of the reviewed studies used mixed samples of both younger and older adults, with ages ranging from 18 to 97 years. Some studies involved advanced age groups, such as middle-aged or older adults, with younger participants [ 6 , 7 , 9 , 10 , 13 - 33 ]. The sample size of surveyed studies ranged from 12 to 404, which varied according to study purpose, data collection method, and analysis plans.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size of surveyed studies ranged from 12 to 404, which varied according to study purpose, data collection method, and analysis plans. Some studies specifically aimed to enroll study participants with depressive mood and relevant mental health problems (7/38, 18%) [ 7 , 9 , 13 , 17 , 23 , 24 , 34 ], other physical health problems or diseases (8/38, 21%) [ 6 , 29 , 31 , 36 , 40 , 43 - 45 ], or chronic pain (2/38, 5%) [ 16 , 25 ], which may be related to depressive mood. Some studies aimed to enroll study participants who had an alcohol or smoking habit (4/38, 11%) [ 22 , 28 , 33 , 46 ] or obesity (2/38, 5%) [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations